Telematic embrace : visionary theories of art, technology, and consciousness - Ascott, Roy (University of California Press, 2003)
Long before e-mail and the Internet permeated society, Roy Ascott, a pioneering British artist and theorist, coined the term "telematic art" to describe the use of online computer networks as an artistic medium. In Telematic Embrace Edward A. Shanken gathers, for the first time, an impressive compilation of more than three decades of Ascott's philosophies on aesthetics, interactivity, and the sense of self and community in the telematic world of cyberspace
Keywords: Computer art.; Art and technology.; Art -- Forecasting.; Art et technologie.; Art -- Prévision.; Art numérique.; ART -- Reference.; ART -- Performance.; Art and technology; Computer art; Esthetica.; Interactie.; Telematica.